INDONESIAN LISTED FIRMS, CORPORATE TAX AVOIDANCE, AND TAX HAVEN: EVIDENCE FROM THE ICIJ OFFSHORE LEAKS DATABASE - Gatot Soepriyanto; Arfian Zudana; Priti Siwa Linggam (Universitas Muhammadiyah Malang, 2020)
This study aims to investigate the involvement of Indonesian firms in tax haven jurisdiction and their corporate tax avoidance activities. Employing Indonesian companies listed in the Indonesia Stock Exchange and the ICIJ Offshore Leaks Database from 2005-2016, this study found that Indonesian companies with tax haven operations as documented in the offshore database have a lower Cash Effective Tax Rate (CETR) and Book Effective Tax Rate (BETR) relative to companies which presumably are unrelated to tax haven jurisdiction based on the leaks data. The results indicate that the effect of having tax haven operations is the reduction of tax payments. Furthermore, as predicted, this study found evidence that companies with tax haven operations as indicated in the ICIJ Offshore Leaks Database have higher cash holdings compared to the counterparts. In this case, those companies also have lower leverage relative to the companies without tax haven operations. Additionally, we also found that firms involved in tax haven operations have a lower return on assets and capital expenditures compared to firms that are not established in a tax haven jurisdiction. In general, those results show that by having operations in tax havens, companies can generate higher cash tax savings to be used for their operations. The findings of this study are significant to identify the characteristics attached to companies with tax haven operations and extend previous literature studies by providing evidence on the characteristics of companies in developing countries which use tax haven operations.